Cancer‐ and Chemotherapy‐Induced Musculoskeletal Degradation. (25th February 2019) - Sturgeon, Kathleen M; Mathis, Katlynn M; Rogers, Connie J; Schmitz, Kathryn H; Waning, David L
ABSTRACT: Mobility in advanced cancer patients is a major health care concern and is often lost in advanced metastatic cancers. Erosion of mobility is a major component in determining quality of life but also starts a process of loss of muscle and bone mass that further devastates patients. In addition, treatment options become limited in these advanced cancer patients. Loss of bone and muscle occurs concomitantly. Advanced cancers that are metastatic to bone often lead to bone loss (osteolytic lesions) but may also lead to abnormal deposition of new bone (osteoblastic lesions). However, in both cases there is a disruption to normal bone remodeling and radiologic evidence of bone loss. Many antitumor therapies can also lead to loss of bone in cancer survivors. Bone loss releases cytokines (TGFβ) stored in the mineralized matrix that can act on skeletal muscle and lead to weakness. Likewise, loss of skeletal muscle mass leads to reduced bone mass and quality via mechanical and endocrine signals. Collectively these interactions are termed bone‐muscle cross‐talk, which has garnered much attention recently as a prime target for musculoskeletal health. Pharmacological approaches as well as nutrition and exercise can improve muscle and bone but have fallen short in the context of advanced cancers and cachexia. This review highlights our current knowledge of these interventions and discusses the difficulties in treating severe musculoskeletal deficits with the emphasis on improving not only bone mass and muscle size but also functional outcomes. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.